Biomanufacturing of bacteriocin-like inhibitory substance producer, lactococcus lactis Gh1, with high stability in freeze-dried form - Jawan, Roslina (2021)
Globally, foodborne illness is still uncontrolled, and outbreaks can result in both health and economic losses. In conjunction with community awareness of the link between lifestyle, diet, and good health, explains the growing demand for functional food products that can improve health beyond the provision of essential nutrition. This scenario encouraged researchers to look for a unique lactic acid bacterium (LAB) with antimicrobial as well as health-promoting traits. In the biomanufacturing of LAB, all the influencing factors are often strain-specific. Therefore, it is important to establish the upstream and downstream processes for mass production of any newly isolated LAB strain. The environment and media compositions strongly influence the growth of LAB and the accumulation of their metabolites such as bacteriocin. In retrieval of the bacteriocin from the culture media, most of the recovery and purification methods are expensive and required several steps in partitioning the final products, which can lead to a decrease in yield. The probiotic application remains a challenge facing the food industry due to the substantial loss of cell viability during the manufacturing, transportation, and prolonged storage of the formulated products. This study was designed to develop a biomanufacturing process started from upstream up to downstream and product development for the production of bacteriocins-like-inhibitory substance (BLIS) from Lactococcus lactis Gh1, a newly isolated LAB from a traditional flavour enhancer. This BLIS- producing LAB was first assessed in vitro, to evaluate its potential applications in the food industry. Subsequently, optimisation of culture conditions and medium composition for improvement of growth and ability of the L. lactis Gh1 to secrete BLIS were conducted in shake flask culture and then transferred into the large scale using stirred tank bioreactor to maximise the product yield. Response surface methodology (RSM) and artificial neural network (ANN) models were employed for medium optimisation. Concurrently, the purification of BLIS for large scale process was carried out to optimise the parameters affecting partitioning of a BLIS in extractive fermentation using aqueous two-phase system (ATPS). In the end, the stability of the freeze-dried cells in the optimal combination of drying medium was examined under different conditions of storage. Results from this study have demonstrated that L. lactis Gh1 was a good candidate as a probiotic bacterium with the ability to coagulate milk, tolerant to NaCl (0.1 - 4.0%, w/v), phenol (0.1 - 0.4%, w/v), bile salt, pH 3 and produced few important enzymes. The absence of haemolytic activity and susceptibility towards ten types of antibiotics ensured the safety of L. lactis Gh1 for human consumption. The antimicrobial activity of BLIS had significant stability at 4 °C in up to 6 months, displayed firmness in four freeze-thaw cycles, did not affected by pH 4 - 8, sensitive to proteinase k, and tolerant to numbers of important food additives. In the cultivation of L. lactis Gh1, the replacement of nitrogen and carbon sources to soytone and fructose, respectively with mid-exponential age of inoculum at 1% (v/v) grown in media with pH 7 increased BLIS production up to 34.94% compared to commercial BHI medium. Subsequently, in medium optimisation, ANN methodology provided better estimation point and data fitting with higher value of R2 and lower value of MAE and RMSE as compared to RSM. BLIS production in optimal medium (717.13±0.76 AU/mL) was about 1.40-fold higher than that obtained in non-optimised (520.56±3.37 AU/mL) medium. BLIS production was further improved by about 1.18 times higher in 2 L stirred tank bioreactor (787.40±1.30 AU/mL) as compared to that obtained in 250 mL shake flask (665.28±14.22 AU/mL) using the optimised medium. The suitable purification of BLIS using extractive ATPS fermentation through RSM modeling was successfully proposed. The scaled up in a 2 L stirred tank bioreactor shows that the maximum recovery rate of BLIS (68.34%), K (0.93) and PF (1.93) were achieved under the conditions of PEG 2000 (10%, w/w)/dextran T500 (8%, w/w) at suitable impeller speed (200 rpm) and pH (pH 7). Sustainable growth of the cells and repeated fermentation up to 8 times (7.35x108 CFU/mL) were observed in this study. In final product preparation, the combination of 10% (w/v) galactose with 10% (w/v) trehalose exhibited the highest survivability rate (91.86±1.54%) and cell viability (7.95x108 CFU/mL) of freeze-dried cells during storage at -30 °C up to day-60. In conclusion, the results of this study demonstrated the potential of L. lactis Gh1 to be used in the food industry. This bacteriogenic LAB has a favourable probiotic property that allows it to be integrated into compatible food matrices. The formulated culture medium and determined influencing fermentation parameters in a 2 L stirred tank bioreactor could be used in larger scale mass production of this probiotic strain. The response of BLIS on extractive ATPS has uncovered the rarely practiced approach in BLIS recovery directly from the fermentation culture which provides a simple yet effective purification procedure. The formulated non-dairy-based protection agents could be utilised to diversify the functional food products, which are useful to vegans, vegetarians, and lactose-intolerant people. The data and information generated from this study could be used to propose a suitable biomanufacturing design for commercial BLIS production by L. lactis Gh1.